A case report on ruptured interstitial ectopic pregnancy: diagnostic dilemma - Sharma, Suman S.; Gokhale, A. V.; Agrawal, Shonali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The ectopic pregnancy occurs when implantation of the blastocyst takes place in a site other than the endometrium of the uterine cavity. Interstitial ectopic pregnancies are gestations that implant within the proximal, intramural portion of the fallopian tubes with high vascularity. Ectopic pregnancy in the interstitial part of the fallopian tubes can be life-threatening considering the thin myometrial tissue surrounding the gestational sac and high vascularization which may result in catastrophic haemorrhage when interstitium is ruptured. Being a hazardous type of ectopic pregnancy, it becomes extremely important to diagnose and manage it. This condition presents a challenge for clinical as well as radiological diagnosis. Generally, a case of interstitial ectopic pregnancy has typical radiological features distinguishing it from other ectopic. The ultrasonographic finding of interstitial line has better sensitivity (80%) and specificity (98%) than eccentric gestational sac location (sensitivity, 40%; specificity, 88%) and myometrial thinning (sensitivity, 40%; specificity, 93%) for the diagnosis of interstitial ectopic pregnancy. Ultrasound is the mainstay of diagnosis, but magnetic resonance imaging can be helpful in unusual or complicated cases. Interstitial ectopic pregnancy rupturing into the leaves of broad ligament and creating a tamponade effect to alter the clinical presentation is a rare event which presents as a diagnostic challenge. Here authors present a case of ruptured interstitial ectopic pregnancy confined to the leaves of broad ligament, with atypical presentation and radiological features which led to difficulty in diagnosing the interstitial ectopic pregnancy. After laparoscopic confirmation of ruptured interstitial ectopic pregnancy, the patient was managed successfully by laparoscopic cornual resection.